CAUSES OF CHRONIC NON-INFECTIOUS DIARRHOEA IN INFANTS LESS THAN 6 MONTHS OF AGE: RARELY RECOGNIZED ENTITIES - Mushtaq, Iqra; Cheema, Huma Arshad; Malik, Hassan Suleman; Waheed, Nadia; Hashmi, Muhammad Almas (Journal of Ayub Medical College Abbottabad, 2017)
Background: Non-infectious causes of chronic diarrhoea are important and easily missed. The study was done with the objectives to identify different causes of chronic non-infectious diarrhoea in infants less than 6 months of age. Methods: All patients less than 6 months of age presenting for the first time to a Paediatric Gastroenterology tertiary care centre with a history of chronic diarrhoea and negative stool cultures, were enrolled over a period of 8 months. Demographical profile and various factors under observation were recorded in this observational study. Collected data was analysed using SPSS version 20. Chi square test was applied as a test of significance for any qualitative variable, p value (p<0.05) was taken as significant. Results: Among 72 enrolled patients, female to male ratio was1.05:1. Age at onset of symptoms was between15 days to 06 months. Aetiology found was Cow’s milk protein allergy (CMPA) in 58 (80.6%), Primary intestinal lymphangiectasia (PIL) 6 (8.3%), Cystic fibrosis (CF) 3 (4.2%), Immunodeficiency (SCID) 2 (2.8%), 1 (1.4%) for each Abetalipoproteinemia (ABL), Glucose galactose malabsorption (GGM) and Congenital chloride diarrhoea (CCD). Conclusions: Among non-infectious causes of chronic diarrhoea in early infancy, cow’s milk protein allergy is most common followed by Primary intestinal lymphangiectasia and Cystic fibrosis. Keywords: Chronic Diarrhoea; Cow’s Milk Protein Allergy; Primary Intestinal Lymphangiectasia; Cystic Fibrosis; Immunodeficiency; Abetalipoproteinemia; Glucose Galactose Malabsorption; Congenital Chloride Diarrhoea